Modification of chitosan with monomethyl fumaric acid in an ionic liquid solution. (6th March 2015) - Wang, Zhaodong; Zheng, Liuchun; Li, Chuncheng; Zhang, Dong; Xiao, Yaonan; Guan, Guohu; Zhu, Wenxiang
Highlights: Monomethyl fumaric acid was selected to modify chitosan in an ionic liquid. Chitosan salt and chitosan amide were obtained. Solubility and antioxidant activity of chitosan have been effectively improved. Abstract: Antibacterial and antioxidant monomethyl fumaric acid (MFA) was selected to modify chitosan, using aqueous solution of an ionic liquid as a homogeneous and green reaction media. The chemical structures of resulting polymers were systematically characterized by 1 H NMR, diffusion ordered spectroscopy, solid 13 C NMR and wide-angle X-ray diffraction. The results show that two kinds of MFA modified chitosan materials with totally different chemical structures have been synthesized. One product was a MF-chitosan salt composed of chitosan cation and MFA anion, which was obtained with the mediation of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N -hydroxysuccinimide. The other one synthesized with the mediation of EDC was a MF-chitosan amide in which MFA and chitosan are covalently attached. Solubility of chitosan has been improved, and MF-chitosan salt can be readily dissolved in water. The antioxidant activity has been enhanced with the introduction of MFA, irrespective of the chemical structure.